(3JGQjN GHf GdYejOs - (3Gdecjf , LQLS Hf GdYejO Hf GdjGS GdeYQha HGdecjf, GdTjN Gdecjf, GHf GdYejO,J (B672 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdCRdi GdChdi HdG GHJOGA hGdCNQ HZjQ GfJgGA s
(3cGf ehLhOkG ai YUQ Gdedc GdXGgQ HjHQSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B122s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B348 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B58 s
(3eUOQ GbJfGA GdCUd (B:s
(3djhf (B(125 or) s
Keywords: (3GdJGQjNs